Psychosocial barriers to medication adherence among older adults living in care homes. - Muhammad Fairuz, Nur Athirah; Loganathan, Mathumalar; Ismail, Hasnah; Usir, Ezlina (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
Medication adherence is important to achieve a better therapeutic outcome, especially in older adults. This study aims to assess medication adherence and its psychosocial barrier among older adults living in care homes. This study aims to identify psychosocial factors which affect the adherence level in older adults. The objectives of this study were to determine the level of medication adherence among older adults living in care homes and to identify the association of psychosocial factors with medication adherence among older adults living in care homes. Methods: A study was conducted in 27 care homes in Klang Valley. A validated questionnaire was used and consisted of three parts: demographic, psychosocial factors and assessment of adherence level. The study only includes those aged 65 years and above, able to speak and hear clearly and taking at least one medication for chronic illness. The interview took 20 minutes per respondent. Data were analysed using the Chi-square and Pearson correlation test to determine the association and correlation between psychosocial factors and adherence level. The p-value is set to <0.05 to indicate the data are statistically significant. Results: A total number of 258 older adults were interviewed and more than half (59.7%) of them were identified as having a low risk of medication non-adherence. There was a statistically significant correlation between receiving enough explanation about the medication (P=0.030) and trust in the physician (P=0.018) with medication adherence. Respondents who received more information on medication dispensed and had a higher trust in physicians were correlated with a lower risk of medication non-adherence. Conclusion: Older adults who received more explanation about medication and had higher trust in their physician were more likely to become adherent to prescribed medicines than those who received little information and had low trust in their physician.